RUTINITAS SARAPAN PAGI MENINGKATKAN PRESTASI BELAJAR ANAK USIA SEKOLAH - Sandri Sandri; Erlisa Candrawati; Ragil Catur A W (Universitas Tribhuwana Tunggadewi, 2015)
The adequacy energy and nutrition can affect learning achievement because intake of energy and nutrient not optimal would affect brain development. One effort providing for the body school aged children for following the lessons in school is to have breakfast nutritious. The study aim is to determine the association between routine breakfast and learning achievements among school aged children. A descriptive correlation design with cross sectional approach was used to 30 4th grade students, and the sample saturated. Data collection techniques used was kuisioner.The method of analysis of data used the kolerasi spearman rank. The research showed that the majority of 4th grade students 19 (63,3%) routinely breakfast and most of 4th grade students 22 (73,3%) have good learning achievements, and statistically significant relationship of routine breakfast with learning achievement. Health education and counseling to family about breakfast behavior needs to be done for increasing student learning achievement.